Realistic Fiction, Experimental Fiction and Culture: A Debate - Kharel, Bijay Kumar (The Saraswati Review, 2024)
Writing fiction of all sorts basically being based on the time-honoured and universal themes has been the kernel literary trend for several centuries. It has ushered as the trend right from the time human beings innately and/or deliberately were in the pursuit of happiness. In its course, writing fiction emerged as a predominant trend from the seventeenth century as an outlet in expressing their feelings and emotion on the one hand and in outpouring their knowledge and experiences of themselves and the world on the other. At the outset, although it happened to be somewhat a kind of spontaneous expression in a saga way, they soon formed a structure and set some tacit parameters of fiction writing. They enhanced some comprehensive and widely accepted characteristics for characters, plot, setting, themes, point of view, conflict, denouement and tone. If a fiction writer or a novelist follows all or most of these characteristics in a set pattern, such writing is generally regarded as the traditional realistic fiction. Further, it values the value system set by the society and culture and presents the theme in an acceptable manner through the use and application of the decent language. As opposed to the norms, experimental writing deconstructs such norms and express what they feel expressing in a chaotic manner. But the question arises to what extent are they to be licensed and given the liberty. As said by T.S. Eliot, a great work is the apt and milestone conglomeration of the tradition and individual talent. Individual talent is pertinent of experimentalism to a considerable extent. Nevertheless, to what extent, one must, should or ought to assimilate the newness. Several experimental novels are highly acclaimed by critics. However, there are several novels that are not worth-reading and worth-teaching especially in an academia on the ground of the theme, setting, tone, language, etc. The novels entailing taboo and vulgar language, having anarchic form and deviated ideas that degrade the social norms and values, etc. should not be prescribed as reading texts at least in an academic institution because a university is not only a platform for setting and shaping knowledge of young scholars, but also a pioneer platform to promote ideals to form a better society.